Impact of organic dairy cattle manure on environmental and egg microbiology of organic free-range laying hens - J.S. Garcia (Elsevier, 2021)
SUMMARY: The popularity of free-range and organic poultry has increased in recent years due to consumer demands. A study was conducted to evaluate how the presence of organic dairy cattle manure could influence the environmental and egg microbiology of organic free-range laying flocks. A flock of brown egg layers was split and maintained in a rotational paddock grazing schedule of which was free of or exposed to organic dairy manure. Environmental and egg sampling occurred approximately every 8 wk between 20 and 44 wk of age for a presence of Listeria spp., Campylobacter spp., Salmonella spp., and enumeration of Enterobacteriaceae. There was no significant difference in the occurrence of Listeria spp., Campylobacter spp. and Salmonella spp. in environmental and egg samples between integrated and control grazing organic free-range flocks. A random sampling of Enterobacteriaceae colonies produced 211 viable isolates for biochemical identification. Seventeen genera, species, or serotypes were identified. There was a greater (P < 0.05) prevalence of total coliforms found on shell emulsion, egg contents, nest box straw, and forage samples from integrated organic free-range compared to control organic free-range flocks. Seasons of the year impacted microbial levels recovered from environmental and egg samples, with which summer having the highest level of all populations monitored. Additional studies are needed to fully understand the effect of mixed production rotational grazing on the prevalence of pathogens and Enterobacteriaceae on organic nest-run eggs and the grazing environment.